Statistics of the Interplanetary Magnetic Field from 0.1 to 30 au. I. Distribution Character - Jiutong Zhao; Shan Wang; Weijie Sun; Xingyu Zhu; Chuanpeng Hou; Qiugang Zong; Jiansen He; Xuzhi Zhou; Chao Yue; Liu Yang (The Astrophysical Journal)
This study investigates the directional and intensity distributions of the interplanetary magnetic field (IMF) across a heliocentric distance range of approximately 0.1–30 au. Measurements from multiple spacecraft reveal that these distributions align closely with the Parker spiral configuration in general. Nevertheless, the deviation from the model is significant and regular. To analyze these deviations, we organized the IMF observations based on the orientation and intensity predicted by the Parker model. The average angular deviation from the Parker spiral increases between 0.1 and 1 au, stabilizing from 1 to 30 au. The magnetic field components perpendicular to the Parker spiral are more likely to lay in the latitudinal and longitudinal directions during the solar maximum and minimum, respectively. The normalized intensity distribution follows a log-normal distribution, with its broadening positively correlated with increasing heliocentric distance. These characteristics cannot be fully attributed to Alfvénic fluctuations or the nonradial component near the potential field source surface. Instead, interactions of flux tubes in the outer heliosphere play a significant role in shaping the IMF. Our results provide a comprehensive assessment of the frequency with which planets encounter non-Parker upstream conditions.